2008
DOI: 10.1002/jrs.2117
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of oxidation and decomposition by SnCl2 in the SERS study of pyridoxine on a roughened Au electrode

Abstract: Severe interference from the oxidation and laser carbonization was encountered in the measurements of surface-enhanced Raman scattering (SERS) spectra of pyridoxine (PN) on the roughened gold electrode. However, we found that high-quality SERS spectra of PN could be obtained by the introduction of SnCl 2 , which only has few Raman peaks at low wavenumbers. SnCl 2 , as a good reductive, is capable of removing the oxidative species on the gold substrate and the dissolved oxygen in solution, and as a result lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It was concluded that molecules of pyridoxine are not "standing up" and that the parallel or tilted orientation is more probable. Chu et al [29] measured SERS spectra on gold, silver and copper electrodes at various potentials. To prevent oxidation and decomposition of pyridoxine, SnCl 2 was added before SERS measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that molecules of pyridoxine are not "standing up" and that the parallel or tilted orientation is more probable. Chu et al [29] measured SERS spectra on gold, silver and copper electrodes at various potentials. To prevent oxidation and decomposition of pyridoxine, SnCl 2 was added before SERS measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies aimed at investigating the adsorption mechanism of nicotinic acid on several surfaces of various silver substrates were published during the last two decades [20][21][22][23][24][25]. Less attention has been paid to riboflavin [26,27], pyridoxine [28,29] and folic acid [30,31], probably because of the complexity of their spectra.…”
Section: Introductionmentioning
confidence: 99%
“…We are pleased by the comparison results of SERS intensity on the nano-networks here and on the best substrates we could prepare by other electrochemical methods such as newly developed potential step [8][9][10] and the classical ORC [7]. It has been demonstrated that the enhancement factor on the substrate prepared by the potential step for 50 s in 2 M HCl was 23.3 times as high as that on a commercially available single-use SERS substrate Klarite™ [10].…”
Section: Resultsmentioning
confidence: 85%
“…Up to present, a number of electrochemical strategies have been developed for fabricating nanostructured gold electrodes for SERS substrates, including roughening gold electrodes with triangular-wave electrochemical oxidation reduction cycles (ORC) [6,7], anodic potential step [8][9][10] and square-wave potential-pulses [11], and templated electrodeposition [12]. Recently, a nanoporous gold film with thickness of approximately 1 μm was made by anodization of gold electrode in an aqueous solution of carboxylic acid or carboxylate [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Recent work on other types of substrates suggests that the SERS performance of these orderly arranged substrates could be optimized by modifying the sizes of trenches and voids and surface roughness in the metal films. [5,6,15] These modifications may be realized by using conventional heating methods (e.g. annealing samples in a heating oven), [16] but the metal and PS films are both heated to high temperatures, resulting in the disfiguration and haphazard arrangement of the PS beads [17] prior to the effective surface modification of metal films.…”
Section: Introductionmentioning
confidence: 99%